Demystifying general anaesthesia - Marshall, Melissa (Operating Room Nurses Association of Canada Journal, 1989)
Are you an operating room nurse who must occasionally help in the recovery room during busy times or after hours? Do you care for patients on a busy surgical floor? Are you a staff nurse working in the post-anaesth- etic care unit or recovery room? Do you ﬂoat to every patient unit in your hos- pital and possibly find yourself alone in the recovery room at 3 a.m. with no resources and a patient emerging from anaesthesia?